Effects of multi-ingredient protein supplementation combined with exercise intervention on body composition and muscle fitness in healthy women: a systematic review with multilevel meta-analysis - Zhou, Chengyu; Qiu, Muen; Zeng, Zhuo; Xie, Qi; Xu, Kai; Yan, Henghao; Wang, Bo; Qiu, Bopeng; Shi, Guoxin (Frontiers in Nutrition, 2025)
ObjectivesThis meta-analysis investigated whether multi-ingredient protein supplements (MIPS) combined with exercise improve body composition and muscle fitness in women. It also examined how participant characteristics, training protocols, and supplementation strategies might influence these outcomes.MethodsA systematic search of five electronic databases was conducted through February 2025 to identify randomized controlled trials evaluating the effects of MIPS combined with exercise training on body composition and muscle-related outcomes in women. A multilevel meta-analysis was performed to pool effect sizes, reported as standardized mean differences (Hedges’ g), with heterogeneity assessed through predefined subgroup analyses.ResultsNine randomized controlled trials involving 408 healthy women aged 18 to 73 years were included. The meta-analysis showed that combining MIPS with exercise training led to significant increases in fat-free mass [0.45 kg (0.19 to 0.71), p = 0.003], muscle hypertrophy [Hedges’ g = 0.35 (0.05 to 0.65), p = 0.027], and muscle strength [Hedges’ g = 0.50 (0.06 to 0.95), p = 0.029]. However, no significant effects were observed on fat mass, body fat percentage, waist circumference, or functional performance (all p > 0.05). Subgroup analyses revealed that gains in fat-free mass were more pronounced among older adults, overweight individuals, participants whose supplement intake was timed near exercise, and those in interventions exceeding 12 weeks (all p < 0.01). Similarly, improvements in muscle hypertrophy and strength were greater in longer interventions and when supplementation was aligned with dietary intake. Younger women showed larger gains in muscle strength, whereas older women experienced more increases in fat-free mass.ConclusionCombining MIPS with exercise training significantly improves fat-free mass, muscle mass, and strength in women, with no additional benefits for fat-related or functional outcomes. These effects are moderated by age, BMI, supplementation timing, isocaloric designs, and intervention duration, highlighting the importance of individualized strategies. Further high-quality isocaloric design trials in diverse female populations are needed to refine tailored approaches that optimize health and performance.Systematic review registrationhttps://osf.io/hkt7p.